The Use of Positive Language on Children Education to Build Children’s Positive Behaviour - Amrina Rosyada; Ayu Bandu Retnomurti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2017)
Language as the basic right of children is the most important thing to build their characters that required from their closest environment, family. Mother is the first person who will put and create the children's characters. The use of positive language by a mother will build on children's positive characters. Therefore, this research aims at determining the use of positive language by mothers in Majelis Taklim Baitul Hasan Jagakarsa, on children education to build their positive behavior. This research employing a cross-sectional survey method with attitudinal questionnaire of ten questions with the total respondents of 118 people. By implementing the formula of positive language, mothers will hopefully understand more the use of positive language on children education.